Investigation of the Effect of Energy Consumption on Carbon Emissions in Azerbaijan in the Context of the Environmental Kuznets Curve - Huseynli, Nigar (International Journal of Energy Economics and Policy, 2024)
There is a close and mutual relationship between environmental problems and economics. While the increase in economic activities causes environmental problems, environmental problems negatively affect sustainable economic growth. The main purpose of this study is to empirically investigate the effect of energy consumption on carbon emissions in the context of the Environmental Kuznets Curve (EKC) hypothesis in the Azerbaijan economy in the period 1997-2021. Data between energy consumption per capita, income per capita and carbon emissions were included in the analysis. The determination of this relationship was investigated by the Granger causality method. As a result of the analysis, it is clear that the Environmental Kuznets Curve Approach is not valid for Azerbaijan.